Materials for electrocatalysts in proton exchange membrane fuel cell: A brief review - Alabi, A. S.; Popoola, A. P. I.; Popoola, O. M.; Mathe, N. R.; Abdulwahab, M. (Frontiers in Energy Research, 2023)
Energy is a requisite factor for technological advancement and the economic development of any society. Currently, global energy demand and supply largely rely on fossil fuels. The use of fossil fuels as a source of energy has caused severe environmental pollution and global warming. To salvage the dire situation, research effort is geared toward the utilization of clean, renewable and sustainable energy sources and the hydrogen energy economy is among the most preferred choices. Hydrogen energy economy, which includes hydrogen production, storage and conversion has gained wide consideration as an ecofriendly future energy solution with a fuel cell as its conversion device. Fuel cells, especially, the proton exchange membrane category, present a promising technology that converts hydrogen directly into electricity with great efficiency and no hazardous emissions. Unfortunately, the current generation of proton exchange membrane fuel cells faces some drawbacks that prevent them from large-scale market adoption. These challenges include the high costs and durability concerns of catalyst materials. The main source of high cost in fuel cells is the platinum catalyst used in the electrodes, particularly at the cathode where the sluggish oxygen reduction reaction kinetics require high loading of precious metals. Many research efforts on proton exchange membrane fuel cells are directed to reduce the device cost by reducing or completely replacing the platinum metal loading using alternative low-cost materials with “platinum-like” catalytic behaviour while maintaining high power performance and durability. Consequently, this review attempts to highlight recent research efforts to replace platinum and carbon support with other cost-effective and durable materials in proton exchange membrane fuel cell electrocatalysts. Overview of promising materials such as alloy-based (binary, ternary, quaternary and high-entropy alloys), single atom and metal-free electrocatalysts were discussed, as the research areas are still in their infancy and have many open questions that need to be answered to gain insight into their intrinsic requirements that will inform the recommendation for outlook in selecting them as electrocatalysts for oxygen reduction reaction in proton exchange membrane fuel cell.